Freestanding mesoporous VN/CNT hybrid electrodes for flexible all-solid-state supercapacitors - Xiao, Xu (Advanced materials (Deerfield Beach, Fla.), 2013)
© 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.